2013
DOI: 10.1016/j.crte.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for the identification of ventifacts in the geological record: A review and new insights

Abstract: Ventifacts are large clasts (pebble-to boulder-sized) shaped by corrasion (sensu Walther, 1900): abrasion by wind-carried particles. As introduced by Evans (1911), this term was restricted to forms showing one or more facet(s) cut by sandblasting (Windkanter in the German literature), but it was extended by Bryan (1931) to include all windworn elements, whether grooved, carved, striated or truly faceted. Most geomorphologists also extend this term to bedrock surfaces (Greeley and Iversen, 1985;Knight, 2008), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…It shows less than ten metres of lateral extension before it disappears due to erosion. It is developed in areas of transition between fluvial to aeolian dominance (Kocurek and Nelson, 1986;Brookfield, 1992;Tripaldi and Limarino, 2008;Durand and Bourquin, 2013). The restricted sediment supply in these transitional areas could be responsible for the lateral development of these lowrelief morphologies (Mountney, 2006), while the variation of wind speed would favour the transition between plane-bed lamination and wind-ripple strata.…”
Section: Aeolian Sedimentary Environmentsmentioning
confidence: 97%
“…It shows less than ten metres of lateral extension before it disappears due to erosion. It is developed in areas of transition between fluvial to aeolian dominance (Kocurek and Nelson, 1986;Brookfield, 1992;Tripaldi and Limarino, 2008;Durand and Bourquin, 2013). The restricted sediment supply in these transitional areas could be responsible for the lateral development of these lowrelief morphologies (Mountney, 2006), while the variation of wind speed would favour the transition between plane-bed lamination and wind-ripple strata.…”
Section: Aeolian Sedimentary Environmentsmentioning
confidence: 97%
“…However, shallow subsurface exploration showed that there is no bedrock to weather, that is, down to 40 cm depth. Based on the literature (Parsons and Abrahams, 1984;Svintsov, 2009;Durand and Bourquin, 2013), such reg-type sites form by in situ weathering and fragmentation of bedrock along with deflation of finegrained products. However, this is not probable here as the bedrock was missing, and thus, in situ weathering could have contributed only in an unusual way (the mixed emergence of other formation methods might contribute and the very long timescale of formation also could make the formation process and the explanation unusual).…”
Section: Shallow Subsurface Explorationmentioning
confidence: 99%
“…The reason for the CIA, CIA*, or CIA-K proxies being less sensitive to palaeoclimate changes in the here studied sections might be best explained by already chemically weathered, preaccumulated Permian siliciclastic debris before its final transport and sedimentation. Late Permian-Early Triassic phases of non-sedimentation, leading to enhanced chemical weathering of the pre-accumulated debris, are documented in the Central European Basin by Early Triassic aeolianites such as occurrences of ventrifacts (e.g., Durand and Bourquin, 2013), aeolian facies architectures like dunes, 'pin-stripe sands' (e.g., Maaß et al, 2010), and single, well rounded, coarse quartz grains as well as patchy distributed, silty to sandy dust (e.g., Hug, 2004). The final Early Triassic transport might be triggered either by tectonic pulses or by changes in palaeoclimate conditions.…”
Section: Major-elementsmentioning
confidence: 99%